2004
DOI: 10.1016/j.cell.2004.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Evolution of Nervous System Genes in the Origin of Homo sapiens

Abstract: Human evolution is characterized by a dramatic increase in brain size and complexity. To probe its genetic basis, we examined the evolution of genes involved in diverse aspects of nervous system biology. We found that these genes display significantly higher rates of protein evolution in primates than in rodents. Importantly, this trend is most pronounced for the subset of genes implicated in nervous system development. Moreover, within primates, the acceleration of protein evolution is most prominent in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
280
1
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(309 citation statements)
references
References 70 publications
22
280
1
6
Order By: Relevance
“…An alternate, albeit related, explanation would be that regions with low genetic variance have greater functional constraints on their determinants of cortical thickness, such that genetic mutations influencing these regions will typically be eliminated quickly from the population through purifying selection. Comparative genomic experiments have shown that a subset of neurally-expressed genes have evolved more rapidly in humans than in other primates [Chimpanzee Sequencing and Analysis Consortium, 2005;Dorus et al, 2004;Khaitovich et al, 2005]; both gene expression changes and protein sequence modification have accelerated in humans relative to nonhuman primates [Caceres et al, 2003;Enard et al, 2002;Gu and Gu, 2003;Hsieh et al, 2003;Uddin et al, 2004]. The findings of increased genetic variance in evolutionarily recent structures may represent a remnant of these rapid neurogenetic changes that accompanied our divergence from other primates.…”
Section: Discussionmentioning
confidence: 99%
“…An alternate, albeit related, explanation would be that regions with low genetic variance have greater functional constraints on their determinants of cortical thickness, such that genetic mutations influencing these regions will typically be eliminated quickly from the population through purifying selection. Comparative genomic experiments have shown that a subset of neurally-expressed genes have evolved more rapidly in humans than in other primates [Chimpanzee Sequencing and Analysis Consortium, 2005;Dorus et al, 2004;Khaitovich et al, 2005]; both gene expression changes and protein sequence modification have accelerated in humans relative to nonhuman primates [Caceres et al, 2003;Enard et al, 2002;Gu and Gu, 2003;Hsieh et al, 2003;Uddin et al, 2004]. The findings of increased genetic variance in evolutionarily recent structures may represent a remnant of these rapid neurogenetic changes that accompanied our divergence from other primates.…”
Section: Discussionmentioning
confidence: 99%
“…J. Craig Venter and over 200 co-authors call the human brain "a massive singularity" (Venter et al 2001(Venter et al , 1347. A team of neurogeneticists conclude: "Human evolution is characterized by a dramatic increase in brain size and complexity" (Dorus et al 2004(Dorus et al , 1027. Bruce Lahn, the lead researcher in the study, was interviewed:…”
Section: Presence: Persons and Beyondmentioning
confidence: 99%
“…Dans ce contexte, l'identification des éphrines comme signaux pro-apoptotiques suggère que ces facteurs pourraient être utilisés dans le contrôle spatial et temporel de la mort cellulaire des progéniteurs, comme cela a été démontré pour certains gènes HOX au cours du développement neural de la drosophile [6]. Par ailleurs, une étude de bio-informatique publiée récemment [7] a montré que des gènes de plusieurs caspases, eux-mêmes régu-lés par les éphrines [2], avaient subi une sélection positive au cours de l'évolution des hominidés. Ainsi, il est tentant de spéculer que des changements évolutifs du contrôle de la mort cellulaire neurale feraient partie des facteurs ayant permis l'émergence d'un cerveau de plus grande taille dans notre espèce.…”
Section: Des Signaux Mortels Qui Contrôlent La Taille Du Cerveauunclassified